Human Bronchial Epithelial Cells Induce CD141/CD123/DC-SIGN/FLT3 Monocytes That Promote Allogeneic Th17 Differentiation - Gazdhar, Amiq; Blank, Fabian; Cesson, Valerie; Lovis, Alban; Aubert, John David; Lazor, Romain; Spertini, Francois; Wilson, Anne; Hostettler, Katrin; Nicod, Laurent P.; Obregon, Carolina (Frontiers in Immunology, 2017)
Little is known about monocyte differentiation in the lung mucosal environment and about how the epithelium shapes monocyte function. We studied the role of the soluble component of bronchial epithelial cells (BECs) obtained under basal culture conditions in innate and adaptive monocyte responses. Monocytes cultured in BEC- conditioned media (CM) specifically upregulate CD141, CD123 and DC-SIGN surface levels and FLT3 expression as well as the release of IL-1β, IL-6 and IL-10. BEC-conditioned monocytes stimulate naive T cells to produce IL-17 through IL-1β mechanism, and also trigger IL-10 production by memory T cells. Furthermore, monocytes cultured in an inflammatory environment induced by the cytokines IL-6, IL-8, IL-1β, IL-15, TNF-α and GM-CSF also upregulate CD123 and DC-SIGN expression. However, only inflammatory cytokines in the epithelial environment boost the expression of CD141. Interestingly, we identified a CD141/CD123/DC-SIGN triple positive population in the bronchoalveolar lavage fluid from patients with different inflammatory conditions, demonstrating that this monocyte population exists in vivo. The frequency of this monocyte population was significantly increased in patients with sarcoidosis, suggesting a role in inflammatory mechanisms. Overall, these data highlight the specific role that the epithelium plays in shaping monocyte responses. Therefore, the unravelling of these mechanisms contributes to the understanding of the function that the epithelium may play in vivo.